Absolute Competence of the State Administrative Court over Onrechtmatige Overheidsdaad Disputes in Indonesia’s 2024 Election - Azzahra Hifz Aldin Fitrada; Pratama Herry Herlambang; Martitah Martitah (Law Research Review Quarterly, 2026)
Decision Number 133/G/TF/2024/PTUN.JKT of the Jakarta State Administrative Court, which declared the lawsuit against the General Election Commission (KPU) inadmissible, has generated debate concerning the limits of the absolute jurisdiction of the State Administrative Court (PTUN) in adjudicating disputes related to onrechtmatige overheidsdaad (OOD) during the electoral process. This article examines the scope of PTUN’s authority over administrative actions undertaken by election management bodies, using the a quo decision as the central object of analysis. This study employs normative legal research through statutory, conceptual, and analytical approaches, based on an examination of the Law on Government Administration, the Election Law, Supreme Court Regulation Number 2 of 2019, and relevant judicial decisions. The findings show that the Jakarta PTUN classified the dispute as an election process dispute governed by the electoral legal regime as lex specialis, thereby excluding the OOD mechanism. The Court reasoned that the KPU’s actions constituted the implementation of Constitutional Court Decision Number 90/PUU-XXI/2023, which is final and binding. This interpretation narrows judicial control over administrative actions in the electoral process. Conceptually, the finality of Constitutional Court decisions attaches to their normative content and operative ruling, not automatically to implementing administrative actions. Therefore, such actions should remain subject to judicial review under the OOD mechanism. Harmonization between the Election Law and the Law on Government Administration is necessary to ensure legal certainty and uphold the rule of law.